Zaamin district-tourism gate of Uzbekistan - Kholmurzayeva, Dilorom (ANTIS PUBLISHER, 2024)
Uzbekistan is one of the countries with great potential and opportunities in the field of tourism. The unique nature of our country, rich cultural and spiritual heritage, historical and memorial monuments have always attracted foreigners.